Evaluation of metal‐organic framework 5 as a new SPE material for the determination of polycyclic aromatic hydrocarbons in environmental waters. Issue 7 (7th March 2013) - Yang, Shaolei; Chen, Chunyan; Yan, Zhihong; Cai, Qingyun; Yao, Shouzhuo
<x xml:space="preserve">Abstract</x> Metal‐organic frameworks, a new class of materials with high surface area and great porosity, have been widely applied in gas sorption. It is generally known that metal‐organic framework 5 cannot be applied in aqueous phase since it is water sensitive. However, this work reveals that the derived material of metal‐organic framework 5 is a good SPE sorbent that can be applied to aqueous phases. Metal‐organic framework 5 was prepared and used as a SPE sorbent for the determination of polycyclic aromatic hydrocarbons in environmental matrices coupling with HPLC. The water treatment induced changes in the properties were investigated in detail. Even though metal‐organic framework 5 is conversed to a second phase after water treatment, it still shows high extraction ability. Under the optimized experimental conditions, good sensitivity levels were achieved with low LODs ranging from 0.4 to 4.0 ng L−1 and a linearity of 0.004–20 μg L−1 (R2 > 0.996) for the investigated polycyclic aromatic hydrocarbons. The method has been validated in the analysis of real water samples with recoveries in the range of 80.2–120.2% and RSDs in the range of 0.5–11.7%.